2017
DOI: 10.1002/oby.21744
|View full text |Cite
|
Sign up to set email alerts
|

Adults with initial metabolic syndrome have altered muscle deoxygenation during incremental exercise

Abstract: MetS, without overt diseases, altered kinetics of muscle deoxygenation during incremental exercise, particularly at high-intensity exercise. Therefore, the balance between utilization and delivery of O within skeletal muscle is impaired early in MetS natural history, which may contribute to the reduction in aerobic power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Exercise is an alternative to increase energy expenditure with (or even without) restricted intake [ 219 , 220 ]. This approach is not always feasible, since obesity is syndromic with cardiovascular disease and problems of mobility [ 221 ] and, despite numerous claims on the contrary, exercise it not sufficient to revert the damages of an established MS [ 222 ], and may not improve the health status [ 223 ]. However, well dosed exercise may provide benefits to mild cases and young patients [ 224 ].…”
Section: Normalization and Regulation Under Excess (If Any)mentioning
confidence: 99%
“…Exercise is an alternative to increase energy expenditure with (or even without) restricted intake [ 219 , 220 ]. This approach is not always feasible, since obesity is syndromic with cardiovascular disease and problems of mobility [ 221 ] and, despite numerous claims on the contrary, exercise it not sufficient to revert the damages of an established MS [ 222 ], and may not improve the health status [ 223 ]. However, well dosed exercise may provide benefits to mild cases and young patients [ 224 ].…”
Section: Normalization and Regulation Under Excess (If Any)mentioning
confidence: 99%
“…Gurd et al ( Gurd et al, 2008 ) also demonstrated slower VO 2 kinetics responses and greater deoxyhemoglobin profile in older adults compared with healthy young adults. Machado et al ( Machado et al, 2017 ) showed that males with metabolic syndrome (MetS) had altered muscle deoxygenation kinetics during incremental exercise. Participants with MetS and age-matched controls performed a progressive and incremental cardiopulmonary exercise test in a cycle ergometer.…”
Section: Integrative Cardiovascular Physiology–insights Into Weakness...mentioning
confidence: 99%
“…Besides that, the quiescent MuSCs also have unique gene expression profiles compared to the activated MuSCs. Genes such as Calcitonin Receptor (CalcR), CD34, α 7 -Integrin, Sprouty 1, Syndecan-4, CXCR4, Integrinβ1 (ITGB1), M-Cadherin, N-Cadherin, Notch Receptor, Osmotically inducible lipoprotein β (OSMβ), and Teneurin transmembrane protein 4 (Tenm4/Odz4) are highly expressed in quiescent MuSCs (Fu et al 2015b , Fukada et al 2013 , Goel et al 2017 , Machado et al 2017a , Machado et al 2017b , van Velthoven et al 2017 , Yamaguchi et al 2012 ).…”
Section: Quiescent Muscsmentioning
confidence: 99%